Influence of flow direction in the performance of anaerobic filters - doi: 10.4025/actascitechnol.v34i2.10353 - Fia, Ronaldo; Schuery, Filipe Cruz; Matos, Antonio Teixeira de; Fia, Fátima Resende Luiz; Borges, Alisson Carraro (Acta Scientiarum. Technology, 2011)
This work aimed to evaluate the performance of similar anaerobic filters operating with opposite wastewater flows, and compare mathematical models that describe the kinetics of organic matter degradation in both. Two pilot-scale filters were fed with domestic effluent - one filter worked as upflow (UAF) and the other as downflow (DAF). Experimental COD data obtained from samples taken along the length of the filters were used to fit the first-order mathematical model, the model proposed by Leduy and Zajic (1973) and the model proposed by Brasil et al. (2007). The first model showed overestimated reaction constant (k) values when compared to those obtained using the other models. The models proposed by Brasil et al. (2007) and Leduy and Zajic (1973) presented the highest coefficients of determination (R2). The average removal efficiencies of total COD were equal to 68 and 79% for UAF and DAF, respectively. The results revealed no significant differences between the two filters with regard to the variables applied.